AUCTORITAS: A Semantic Web-based tool for Authority Control - Tabares Martín, Leandro; Fernández Peña, Félix Oscar; Leiva Mederos, Amed Abel (My University, 2018)
Authority control is recognized as an expensive task in the cataloging process. This is nowadays an active research field in libraries and related research institutions even when several approaches have been proposed in this research area. In this paper, we propose AUCTORITAS, a tool for exposing high value services on the web for the authority control in a generic institution environment. This paper describes AUCTORITAS' web services, its Ontology-based Data Access model and how the semantic web languages make possible the semantic integration of heterogeneous data sources.
Keywords: Control de Autoridades